A Critical Evaluation of English for Informatics ESP Textbook At Department of Informatics and Technology of University of Ma’arif Nahdlatul Ulama (UMNU) Kebumen - Hastri Firharmawan (Universitas PGRI Semarang, 2016)
Having foremost significance in any ESP classroom, course readings are known as one of the most visible parts of any ESP instructing program. Playing a vital part where English is used as an outside dialect, such reading material ought to have a few highlights on which the needs and targets of an ESP teaching program are met. Concerning such a significance, making use of McDonough and Shaw’s (2003) model, this study evaluate fundamentally the current status of the ESP book used in English for informatics at UMNU Kebumen. The evaluation tries:1)to show the significance of ESP materials development as well as evaluation; (2) to present the fundamental drawbacks in the book; and, (3) to show some practical recommendation and arrangements to handle the noteworthy issues and drawbacks of such ESP textbooks.